Baseline swallowing measures predict recovery at 6 weeks after transoral robotic surgery for head and neck cancer. (19th September 2016) - Owen, S.; Puvanendran, M.; Meikle, D.; Bowe, I.; O'Hara, J.; Patterson, J.; Paleri, V.
Abstract : Objectives: To explore whether pre‐treatment swallowing measures predict swallowing recovery at 6 weeks after transoral robotic surgery (TORS). Design: Prospective cohort study. Setting: Tertiary care cancer centre in the United Kingdom. Participants: Fifty‐one consecutive patients undergoing TORS for head and neck cancer, between April 2013 and February 2015. Main outcome measures: Swallowing function assessed by Performance Status Scale (PSS) Normalcy of Diet, timed water swallow test capacity scores (WST) and duration of tube feeding. Results: The primary site distribution was as follows: 21 oropharynx, 8 larynx, 6 mucosectomy and 6 hypopharynx. T stages included 7 staged Tx, 21 T1–T2 tumours and 1 T3 tumour. Moderate‐to‐severe comorbidity was found in 45/51 patients. Mean PSS score was 83 (sd 27.54); mean WST score was 11.14 (sd 7.97). Most patients (73%) required tube feeding post‐operatively, with mean tube feed duration of 18.08 days (sd 17.91); 76% resumed oral intake by 6 weeks. Pre‐treatment swallow tests showed moderate negative correlation with tube feeding duration: PSS ( rho 0–.430, P = .003); WST ( rho 0–.503, P = 0.002). Conclusions: The majority of TORS patients resume oral intake by 6 weeks. This study shows that impaired swallowing prior to surgery correlates with post‐operative duration of tube feeding and strengthens the evidence for the utility of these measures in this clinical setting.